Posisi Ibu Hamil Memengaruhi Akurasi Pengukuran Kesejahteraan Janin: Position of Pregnant Women Effects on Accuracy of Fetal Heart Rate Measurement - Minarti, Minarti; Risnawati, Risnawati (Jurnal Bidan Cerdas, 2020)
During pregnancy, the fetal heart rate is a picture of the well-being of the fetus in the womb. The mother's position affects the results of the assessment when taking measurements of the fetal heart rate. The purpose of this study is to determine the accuracy of the measurement of fetal well-being based on the position of pregnant women. This type of research is analytic observational in Wajo Health Center, Katobengke Health Center, and Sulaa Health Center, from April - August 2019. The population in this study were all pregnant women registered in the KIA book. The research sample consisted of 60 respondents using inclusion criteria. The data analysis uses univariate analysis. The results showed there were differences in the value of the fetal heart rate measurements for each position. The average value (min-max) of DJJ measurement with the lying position (supine) 128-158 times per-minute, mean value 138.81 times per-minute; sitting position 124-158 times per-minute, mean value 143.41 times per-minute; standing position 126-159 times per-minute, mean value 145.58 times per minute. In a sitting and lying position, the resulting heart rate is in the normal range of 120-140 times per-minute; in a standing position, the heart rate obtained 150-160 times per-minute has the potential for tachycardia. The conclusion of this study is that the position of pregnant women affects the results of fetal heart rate measurement and the good position of the FHR measurement when lying on her back